Tindak Tutur Direktif pada Anime Blue Lock: Directive Speech Acts in The Anime Blue Lock - Hutagaol, Rebecca (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
Blue Lock is a soccer themed anime that is going to be the main focus of this research. The purpose of this research is to identify the various forms of illocutionary directive speech act in the Blue Lock anime along with the speech event that explains the context of the speech. The method used in this research is an analytic descriptive with a qualitative approach and attentive observation method then note taking technique to gather the data. The theories that are applied to this research are directive speech act theory according to Iori (2000) and speech event theory according to Dell Hymes (1974). From this research a total of 22 datas are gathered. The datas are classified into five types of directive speech act. There are 12 datas for command form of speech act, six datas for request form, one data for prohibition form, one data for permission form, and two datas for recommendation form.